Lipid metabolic disorders and their impact on cartilage endplate and nucleus pulposus function in intervertebral disk degeneration - Ruixia Wu; Xiao Juan Zhao; Yaxin Du; Yizhi Dong; Xinyue Song; Yong Zhu (Frontiers in Nutrition)
Lipid metabolism encompasses the processes of digestion, absorption, synthesis, and degradation of fats within biological systems, playing a crucial role in sustaining normal physiological functions. Disorders of lipid metabolism, characterized by abnormal blood lipid levels and dysregulated fatty acid metabolism, have emerged as significant contributors to intervertebral disk degeneration (IDD). The pathogenesis of IDD is multifaceted, encompassing genetic predispositions, nutritional and metabolic factors, mechanical stressors, trauma, and inflammatory responses, which collectively facilitate the progression of IDD. Although the precise mechanisms underlying IDD remain incompletely elucidated, there is substantial consensus regarding the close association between lipid metabolism disorders and its development. Intervertebral disks are essential for maintaining spinal alignment. Their primary functions encompass shock absorption, preservation of physiological curvature, facilitation of movement, and provision of stability. The elasticity and thickness of these disks effectively absorb daily impacts, safeguard the spine, uphold its natural curvature and flexibility, while also creating space for nerve roots to prevent compression and ensure normal transmission of nerve signals. Research indicates that such metabolic disturbances may compromise the functionality of cartilaginous endplates (CEP) and nucleus pulposus (NP), thereby facilitating IDD’s onset and progression. The CEP is integral to internal material exchange and shock absorption while mitigating NP herniation under mechanical load conditions. As the central component of intervertebral disks, NP is essential for maintaining disk height and providing shock-absorbing capabilities; thus, damage to these critical structures accelerates IDD progression. Furthermore, lipid metabolism disorders contribute to IDD through mechanisms including activation of endoplasmic reticulum stress pathways, enhancement of oxidative stress levels, induction of cellular pyroptosis alongside inhibition of autophagy processes—coupled with the promotion of inflammation-induced fibrosis and fibroblast proliferation leading to calcification within intervertebral disks. This review delineates the intricate interplay between lipid metabolism disorders and IDD; it is anticipated that advancing our understanding of this pathogenesis will pave the way for more effective preventive measures and therapeutic strategies against IDD in future research.